John Donne, body and soul - Targoff, Ramie (University of Chicago Press, 2008)
John Donne, one of the most brilliant poets and preachers of the English Renaissance, lived a life full of dramatic changes of fortune, and his writing reflects his wide range of experiences. His collected works vary from passionate love poems to devotional sonnets, from quiet meditations to caustic satires, and from decorous elegies to thundering sermons. For centuries readers have struggled to fuse the seemingly scattered pieces of Donne's life into a complete image of the poet and priest that does not depend on a radical division between the two. In John Donne, Body and Soul, Ramie Targoff.